Effects of omecamtiv mecarbil on the contractile properties of skinned porcine left atrial and ventricular muscles - Nakanishi, Tomohiro; Oyama, Kotaro; Tanaka, Hiroyuki; Kobirumaki-Shimozawa, Fuyu; Ishii, Shuya; Terui, Takako; Ishiwata, Shin’ichi; Fukuda, Norio (Frontiers in Physiology, 2022)
Omecamtiv mecarbil (OM) is a novel inotropic agent for heart failure with systolic dysfunction. OM prolongs the actomyosin attachment duration, which enhances thin filament cooperative activation and accordingly promotes the binding of neighboring myosin to actin. In the present study, we investigated the effects of OM on the steady-state contractile properties in skinned porcine left ventricular (PLV) and atrial (PLA) muscles. OM increased Ca2+ sensitivity in a concentration-dependent manner in PLV, by left shifting the mid-point (pCa50) of the force-pCa curve (ΔpCa50) by ∼0.16 and ∼0.33 pCa units at 0.5 and 1.0 μM, respectively. The Ca2+-sensitizing effect was likewise observed in PLA, but less pronounced with ΔpCa50 values of ∼0.08 and ∼0.22 pCa units at 0.5 and 1.0 μM, respectively. The Ca2+-sensitizing effect of OM (1.0 μM) was attenuated under enhanced thin filament cooperative activation in both PLV and PLA; this attenuation occurred directly via treatment with fast skeletal troponin (ΔpCa50: ∼0.16 and ∼0.10 pCa units in PLV and PLA, respectively) and indirectly by increasing the number of strongly bound cross-bridges in the presence of 3 mM MgADP (ΔpCa50: ∼0.21 and ∼0.08 pCa units in PLV and PLA, respectively). It is likely that this attenuation of the Ca2+-sensitizing effect of OM is due to a decrease in the number of “recruitable” cross-bridges that can potentially produce active force. When cross-bridge detachment was accelerated in the presence of 20 mM inorganic phosphate, the Ca2+-sensitizing effect of OM (1.0 μM) was markedly decreased in both types of preparations (ΔpCa50: ∼0.09 and ∼0.03 pCa units in PLV and PLA, respectively). The present findings suggest that the positive inotropy of OM is more markedly exerted in the ventricle than in the atrium, which results from the strongly bound cross-bridge-dependent allosteric activation of thin filaments.